Peningkatan Literasi Nutrisi Anak Sekolah Dasar melalui Pembelajaran IPA pada Kurikulum Merdeka - Dindin Nasrudin M.Pd; Mila Faizatul Millah; Imelda Helsy; Hamdan Sugilar (LPPM Universitas Terbuka, 2023)
Every people, including elementary school children, need nutritional literacy. This study aims to develop a science learning design to increase students' nutritional literacy in the Merdeka curriculum. This research and development study uses the ADRRI (Analyze, Design, Review, Revision, Implementation) cycle model. This research successfully analyzed the science curriculum in both K13 and the Merdeka Curriculum regarding the relevance of elementary science learning in increasing nutritional literacy. This research also successfully developed a framework and design for elementary science learning to improve students' nutritional literacy. This study recommends that elementary school teachers implement this learning design on the topic of digestive organ systems and circulatory organ systems.